Healthy APBN, proper governance, realizing independent villages for the country - Octavia, Sandra Gadis (Maliki Interdisciplinary Journal, 2024)
The current village funds allocation is 72 trillion.However, The willingness of this fund has not been able to give the optimal results to move the village towards the more progressive direction.Then, Plural problems in this village need to be discussed more deeply, Like improving the quality of government performance that became a path in allocation of funds, Making proper planning for the provided funds allocation so that it's directed in target determination, maximizing planning mapping with a firm commitment to realizing the realization of every designated target, and the village fund movement as an implementation of the village independent to achieve the nation's hope.